Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
-3
Step-by-step explanation:
5x³ + 2 , when x = -1
5(-1)³ + 2
= -5 + 2
= -3
Answer:
-3
(first option listed)
Step-by-step explanation:
we know that 5x³ + 2 is our expression
we want to "evaluate" (find/solve for) when x = -1
we can do this by plugging in -1 to the expression:
5x³ + 2 {note, x = -1}
5(-1)³ + 2 {-1³ = -1}
5(-1) + 2
(-5) + 2
-5 + 2 = - 3
so, when x = -1, the statement is equivalent to -3
hope this helps! :)
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.